Penerapan Model Kooperatif Tipe Jigsaw Untuk Meningkatkan Pemahaman Siswa - Yulianita, Ani; Setyaningsih, Ayu (Ta'lim: The Islamic Religious Educational Journal, 2025)
In the learning process, students' understanding is the key to success and completeness of learning. One of the supporting factors for students to understand the learning material is the use of effective learning models. Based on the initial research conducted on eleventh-grade students at SMKS Wahana Bakti, the students' understanding of Islamic Religious Education (PAI) subjects is still considered low. This study aims to determine how the Jigsaw type cooperative model applies to improve the understanding of eleventh-grade students on the material of modern Islamic civilization at SMKS Wahana Bakti. The Jigsaw type cooperative model is one that involves students more in the learning process. This type of research is classroom action research (CAR) conducted in two cycles. This research was conducted at SMKS Wahana Bakti, with the research subjects being 14 students from the eleventh grade. The instruments used were learning tests and observations. The data analysis technique used is quantitative descriptive analysis technique. Based on the research results, the application of the Jigsaw type cooperative model can improve students' understanding of Islamic civilization material in the modern era for class XI at SMKS Wahana Bakti. This is evidenced by the test results showing an increase in student performance. In the pre-cycle, 28% of students completed the work, in cycle 1 it was 71%, and in cycle 2 it increased to 93%. Through this research, the author hopes that the school and its educators will apply the Jigsaw cooperative model in the learning activities of other subjects.